English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2(a-8)+7=5(a+2)-3a-19

2007-02-04 22:16:32 · 5 answers · asked by tony t 1 in Science & Mathematics Mathematics

5 answers

2(a - 8) + 7=5(a + 2) - 3a - 19

2a - 16 + 7 = 5a + 10 - 3a - 19

2a - 5a + 3a = 10 - 19 + 16 - 7

0 = 0

-∞ < a < ∞

So plugging anything into "a" will satisfy the equation as a proof.

2007-02-04 22:21:04 · answer #1 · answered by wootness 2 · 0 0

2(a - 8) + 7=5(a + 2) - 3a - 19
2a - 16 + 7 = 5a + 10 - 3a - 19
2a - 5a + 3a = 10 - 19 + 16 - 7
0 = 0

2007-02-05 06:29:05 · answer #2 · answered by Anonymous · 0 0

this is the first part
2(a-8) = 2a-16+7=(2a-9)

this is the second part
5(a+2)=5a+10-3a-19 you have to combine like terms
5a-3a+10-19=(2a-9)
so when you put the two parts together you get
2a-9=2a-9
subtracting 2a from both sides gives 0
adding 9 to both sides leaves 0
so the answer is 0=0

2007-02-05 06:30:19 · answer #3 · answered by Anonymous · 0 0

a=0
2*(-8)+7=-9 10-19=-9

2007-02-05 06:28:05 · answer #4 · answered by santmann2002 7 · 0 0

LHS = 2a - 9
RHS = 2a - 9
hence, LHS = RHS.

2007-02-05 06:35:29 · answer #5 · answered by Under-Dog 1 · 0 0

fedest.com, questions and answers